A study on the properties of rice husk reinforced bioplastic - Martin, Hii Chun Yeong (2017)
About 408,000 metric tonnes of rice husk are produced annually yet are not utilise properly as small amount of rice husk is used for fertiliser and the rest become waste. This action leaks to waste disposal problem and high methane emissions. In agriculture, biodegradable plastics are desirable alternative to the current black low density poly(ethylene) plastic. Therefore, a research on bio-polybag is carried out with the objectives to utilize agricultural biomass for the production of biodegradable polybag and to investigate the properties of obtained polybag in terms of mechanical properties, surface structure, and biodegradability. The biomass studied in this research are rice husk due to it abundance in Malaysia, and polylactic acid is used to mix with the biomasses in different compositions (10%, 30%, 50%, 70% and 90%). Three main tests including tensile strength test, Scanning Election Microscopy (SEM) and accelerated aging test are taken place to study the properties. As a result, 30% rice husk: 70% PLA is the best among the ratio, in terms of lower tensile strength, higher elasticity, and shows bigger void and gap. 30% rice husk: 70% PLA has the tensile strength of 11.3 MPa, tensile modulus at 322.12MPa, elongation at break at 3.508%, decomposite rate of 1.413% and SEM test shows many gaps yet with maximum used of biomass material. Hence, 30% rice husk: 70% PLA is the most suitable biomass to use as biodegradable polybag.